Second Breast‐Conserving Treatment for Ipsilateral Breast Tumor Recurrence: A Review of Patient Selection, Reirradiation Techniques, and Clinical Outcomes - Cezara Cheptea; Youlia Kirova; Radu Iulian Mitrica; Mihaela Badea; Pierre Loap (International Journal of Cancer, 2026)
ABSTRACT Local recurrence after primary breast cancer treatment remains a complex clinical scenario in patients previously treated with breast‐conserving therapy and radiotherapy. For decades, salvage mastectomy was considered the standard treatment for ipsilateral breast tumor recurrence, largely because of concerns about local control after repeat lumpectomy and cumulative toxicity after reirradiation. This paradigm has progressively changed. Retrospective comparative series, prospective Phase II data, large multicenter brachytherapy cohorts, and population‐based analyses suggest that second breast‐conserving treatment combined with reirradiation can achieve favorable local control and survival in carefully selected patients, without an apparent survival impact compared with mastectomy. The strongest evidence supports partial breast reirradiation after complete resection of small, unifocal recurrences occurring after a sufficient interval from prior radiotherapy. External beam radiotherapy, multicatheter brachytherapy, and intraoperative radiotherapy each offer distinct technical advantages, toxicity profiles, and levels of evidence. Across modalities, outcomes are most favorable in patients with limited disease, complete resection, long interval from initial treatment, and favorable tumor biology, whereas early recurrence, gross residual disease, skin or chest wall involvement, and adverse molecular subtype are associated with poorer outcomes. Risk stratification tools, including the GEC‐ESTRO APBI classification and TAM score, may help refine patient selection, but practice remains heterogeneous and cumulative dose constraints are not standardized. Future studies should define optimal reirradiation techniques, normal tissue constraints, integration with modern systemic therapies, and patient‐reported outcomes. Second breast‐conserving treatment should therefore be viewed as a personalized alternative to salvage mastectomy in selected patients, rather than as a universal replacement.